MODULAR DEVELOPING EDUCATION SYSTEM IN THE PROCESS OF FORMING THE STUDENTS’ ACTIVITY - Мельничук, Елена; Шарапанюк, А.Й. (Modern engineering and innovative technologies, 2022)
he article reveals the formation of a modular developing system, which is presented as an alternative to the current education system. Features and advantages of the modular system of training are analyzed. The complex of methodological support of the mod